The international collision regulations in the context of international law and the municipal law of the United Kingdom and of South Africa: a critical analysis - Siddle, A M (Department of Public Law, 2023)
The object of this paper is to examine one aspect of safety at sea, namely, the prevention of collisions, and to consider in this regard the role of the International Regulations for Preventing Collisions at Sea. our concern is primarily with the regulatory and preventative aspects of the law (in both the, international and municipal spheres) and not so much with private law aspects, in so far as the latter are concerned with the determination of rights and liabilities as between individuals. This is not to say that private law is irrelevant for our purposes: in the first place, the Collision Regulations are usually considered by the courts in the context of delictual actions in private law, and these cases therefore constitute the most important source of judicial interpretation of the Regulations; secondly, since the Collision Regulations do play a part in the determination of civil liability, the role of private law as an indirect means of enforcement of the Regulations cannot be ignored. The Collision Regulations are of interest from a number of points of view. Firstly, they are of interest in the context of public international law: they are intended to regulate navigation at an international level, and being the product of agreement between states; also, the regulations give rise to questions of state jurisdiction. Secondly, the regulations are important in the context of municipal law; here we are concerned with the manner in which the regulations are enforced. Two states have been singled out for consideration in this regard: the Republic of South Africa, and the United Kingdom, on account of the historical role played by it in collision prevention, and also on account of the close links between the relevant law of that state and of South Africa. The experience and practice of the United Kingdom provides a useful guide and model for South Africa, and is relevant also for comparative purposes. Thirdly, the Regulations are, of course, of vital importance to the mariner. Finally, in a peripheral fashion, the Regulations are of interest to the legal historian, as they represent the legal response to a set of circumstances as they changed over the centuries.